Captains of War: History in Professional Military Education. Issue 7 (9th November 2020) - Halewood, Louis; Morgan-Owen, David
Abstract : This article examines the role of history in professional military education (PME) in light of the recent US Joint Chiefs of Staff's guidance on achieving 'intellectual overmatch'. Louis Halewood and David Morgan-Owen argue that a narrow approach to the past, underpinned by preconceived notions of 'relevance', undermines what ability history has to serve the aims of military education. History need not be 'applied' to make it valuable, as its study can provide a broader understanding of warfare. Only by treating history more seriously, and by meaningfully engaging with the legacies of Britain's own military past, can the discipline contribute to modern PME. ◼